Pengaruh Jumlah Wisatawan Mancanegara Melalui Transportasi Laut, Jumlah Wisatawan Domestik Melalui Transportasi Udara dan Tingkat Penghunian Kamar Hotel Terhadap Pertumbuhan Ekonomi di Bali Pada Masa Pandemi Covid-19 - oeliestina, oeliestina (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2021)
This study aims to determine the effect of the number of foreign tourists via sea transportation, the number of domestic tourists via air transportation and hotel room occupants on economic growth in Bali during the Covid-19 pandemic. This research uses multiple regression analysis method. Data obtained from BPS Bali Province, the period of this research is from 2018 to 2020. The results show that the number of foreign tourists via sea transportation and the number of domestic tourists via air transportation have no significant effect on economic growth in Bali. Meanwhile, hotel room occupancy has a significant effect on economic growth in Bali. This is due to the small number of tourists visiting Bali via sea transportation, many of whom are tourists who use air transportation, the decline in economic growth in Bali because many people have lost their jobs, companies that generate sales and less spending for the country's economy like all decreased, when hotel occupancy decreased, there was a lack of visits to Bali resulting in a drastic decline in economic growth. Therefore, the tourism sector since the Covid-19 pandemic has required a long time and the right policies so that this sector can recover quickly. Keywords: International Tourists Through Sea Transportation, Domestic Tourists Through Air Transportation, Hotel Room Occupancy Rate, Economic Growth of Bali Province